Electroactive substrates for surface-enhanced Raman spectroscopy based on overgrown gold-nanoparticle arrays by electrodeposition on indium tin oxide. Issue 5 (20th February 2023) - González-Pato, Nerea; Rodriguez, Xavier Rodriguez; Pellizzi, Nicola; Fasolato, Claudia; Guasch, Judith; Postorino, Paolo; Veciana, Jaume; Goñi, Alejandro R.; Ratera, Imma
Abstract : Highly homogeneous and robust SERS conductive surfaces with large gold coverages and small inter-particle distances for a combined electrochemical-SERS investigation to monitor switchable redox molecules and electroactivated interfacial reactions. Abstract : We report an easy and low-cost method for the preparation of highly homogeneous electroactive substrates that can be used simultaneously for surface-enhanced Raman spectroscopy (SERS) and electrochemical measurements. The choice of conductive indium tin oxide (ITO) as a substrate is based on its excellent electrical conductivity and transparency. However, its typically high roughness makes the subsequent metal deposition with traditional methods very challenging, making them time-consuming and costly. To circumvent this problem, we developed a simple two-step procedure consisting of first the deposition of a quasi-hexagonal pattern of homogeneously distributed gold nanoparticles (AuNPs) by block-copolymer micellar lithography on ITO. Subsequently, the AuNPs act as seeds for further gold growth by electrodeposition on the pre-patterned ITO substrate. In this way, we reproducibly achieved substrates (>50) with an average gold coverage of (40 ± 5) % and many hot spots due to a small average inter-particle distance of (15 ± 5) nm. These substrates exhibit a strong and homogeneous Raman signal, as determined using 2D maps obtained with the standard Raman tag molecule 4-mercaptobenzoic acid. Moreover, the electrochemical performance of the developed conductive SERS substrates was demonstrated using a Michael addition reaction monitored by Raman scattering. This reaction occurs between the hydroquinone/benzoquinone redox pair and a biologically relevant analyte, but only takes place in one of the redox states of the hydroquinone/benzoquinone system.